Diet and behavior of the burrowing owl (Athene cunicularia) in Atiquipa, an ecosystem of Lomas in the south of Peru - César Luque Fernández (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Luque-Fernández CR. 2019. Diet and behavior of the burrowing owl (Athene cunicularia) in Atiquipa, an ecosystem of Lomas in the south of Peru. Biodiversitas 20: 137-143. The study of trophic and behavioral habits is a fundamental aspect in the knowledge of the natural history of species, especially for those that present a wide range of distribution and that have to adapt to the habitats and available resources that can find to survive. The diet and behavior of Athene cunicularia were studied in a peculiar ecosystem such as the lomas formation, on the arid coast of southern Peru. The analysis of regurgitated pellets from a family group of Athene cunicularia was used and complemented with the monitoring of behavior through the use of trap cameras and direct observations. The results show that the diet during the months of study was based on a high proportion of invertebrate beetles (Tenebrionidae) and scorpions, also finding remains of vertebrates, including rodents, birds and highlighting the presence of a species of marsupial mouse. On the study of behavior, marked and recurrent activities are established during the day for this species, where grooming sessions are frequently reported, as well as interaction with a possible predator of this owl species. These results contribute to the understanding of the trophic relationship and its role in the studied lomas ecosystem, which is added to the importance of this species in the conservation of diversity in desert ecosystems.